Films in Health Sciences Education. Learning through moving images (eBook) - Donaghy , Kieran (BIBLIOTECA UNIVERSITÀRIA, 2012)
Films in Health Sciences Education combines the study of medical themes and film analysis. Subjects related to health care of interest to doctors, nurses, pharmacists and psychologists among others, are presented alongside an analysis of film language. The ten films analysed in the book all deal with a disease or health problem that is relevant to the plot, they cover a wide range of pathologies and include patients of all ages.